2014
DOI: 10.5539/mas.v8n4p37
|View full text |Cite
|
Sign up to set email alerts
|

Municipal Solid Waste Management and Potential Revenue from Recycling in Malaysia

Abstract: Municipal Solid Wastes (MSW) issues have become talk of the day worldwide because of the current and the future threats it has to both life and the environment. Malaysia, like other developing nations, has been facing serious problems in recent years in terms of MSW and its management due to the nation's rapid economic growth. The objective of this paper is to review and present the current state of MSW and its management in Malaysia and to estimate the economic potentials of some recyclables as well. MSW gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…Study by authors [31] showed that the number of recycle bins need to be increased to improve the recycle rate among the household in Kuala Lumpur, Malaysia. ReCellular and Rechargeable Battery Recycling Corporation (RBBC) which is a non-profit organisation has established a collective service around the country in Brazil to collect the obsolete cell phones and the results showed that the e-waste recycling rate has successfully increased [36]. Infrastructure also important in encourage the community to foster e-waste recycling behaviour.…”
Section: 5e-wastementioning
confidence: 98%
“…Study by authors [31] showed that the number of recycle bins need to be increased to improve the recycle rate among the household in Kuala Lumpur, Malaysia. ReCellular and Rechargeable Battery Recycling Corporation (RBBC) which is a non-profit organisation has established a collective service around the country in Brazil to collect the obsolete cell phones and the results showed that the e-waste recycling rate has successfully increased [36]. Infrastructure also important in encourage the community to foster e-waste recycling behaviour.…”
Section: 5e-wastementioning
confidence: 98%
“…This indicates that there is degradation of the substrate and the stabilization of compost also occurred. These parameters are within the range required for agricultural use as soil amendment agreed as [24][25][26][27]. The data above showed significant indicator that the product of food waste compost gain from this study is not at an optimum level compare to use of standard compost as fertilizer which is 23: 1 (Kim et al, 2008) [14].…”
Section: Elemental Analysis Using Chns Analyzermentioning
confidence: 99%
“…For over the decade, various procedure with preference targets on solid waste management in Malaysia were proposed such as recycling, composting, incineration and others (ordinary dumping) yet low level of accomplishment showed up until today specifically on composting rate is zero to only 1% from the year 2002 to 2006. In the year 2020, the government planned to reduce the landfilling to 50%, by increasing composting to (1) as supported by other study stating biological utilization in degrading organic waste was more proper solution method compared to other treatments such as landfill and incineration in dealing with the organic waste (2). The two largest problems faced by the composting process are odour and leachate where the both of them often correlate with the deficiency of process management.…”
Section: Introductionmentioning
confidence: 99%